The role of the superficial region in determining the dynamic properties of articular cartilage. - KELLY, DANIEL JOHN; GANNON, ALANNA (My University, 2012)
OBJECTIVE: The objective of this study was to elucidate the role of the superficial region of articular cartilage in determining the dynamic properties of the tissue. It is hypothesised that removal of the superficial region will influence both the flow dependent and independent properties of articular cartilage, leading to a reduction in the dynamic modulus of the tissue. METHODS: Osteochondral cores from the femoropatellar groove of three porcine knee joints were subjected to static and dynamic loading in confined or unconfined compression at increasing strain increments with and without their superficial regions. Equilibrium moduli and dynamic moduli were measured and the tissue permeability was estimated by fitting experimental data to a biphasic model. RESULTS: Biochemical analysis confirmed a zonal gradient in the tissue composition and organisation. Histological and PLM analysis demonstrated intense collagen staining in the superficial region of the tissue with alignment of the collagen fibres parallel to the articular surface. Mechanical testing revealed that the superficial region is less stiff than the remainder of the tissue in compression, however removal of this region from intact cores was found to significantly reduce the dynamic modulus of the remaining tissue, suggesting decreased fluid load support within the tissue during transient loading upon removal of the superficial region. Data fits to a biphasic model predict a significantly lower permeability in the superficial region compared to the remainder of the tissue. CONCLUSIONS: It is postulated that the observed decrease in the dynamic moduli is due at least in part to the superficial region acting as a low permeability barrier, where its removal decreases the tissue's ability to maintain fluid load support. This result emphasises the impact that degeneration of the superficial region has on the functionality of the remaining tissue.
PUBLISHED
Keywords: superficial region; superficial region